Link between anisotropic electrochemistry and surface transformations at single‐crystal silicon electrodes: Implications for lithium‐ion batteries. Issue 2 (13th March 2023) - Martín‐Yerga, Daniel; Bahri, Mounib; Curd, Matthew E.; Xu, Xiangdong; Li, Weiqun; Burnett, Timothy L.; Withers, Philip J.; Mehdi, B. Layla; Browning, Nigel D.; Unwin, Patrick R.
Abstract: Silicon is a promising negative electrode material for high‐energy‐density Li‐ion batteries (LiBs) but suffers from significant degradation due to the mechanical stress induced by lithiation. Volume expansion and lithiation in Si are strongly anisotropic but associated early interfacial transformations linked to these phenomena and their implications for electrode performance remain poorly understood. Here we develop a novel correlative electrochemical multi‐microscopy approach to study local interfacial degradation at the early stages for three different surface orientations of Si single crystals: Si(1 0 0), Si(1 1 0) and Si(3 1 1), after Li‐ion electrochemical cycling. The experimental strategy combines scanning electrochemical cell microscopy (SECCM) measurements with subsequently recorded scanning transmission electron microscopy images of high‐quality cross sections of Si electrodes, extracted at selected SECCM regions, using a novel Xe + plasma‐focused ion beam procedure. These studies reveal significant surface orientation–dependent nanoscale degradation mechanisms that strongly control electrode performance. Si(1 0 0) was immune to interfacial degradation showing the best lithiation reversibility, whereas local nanoscale delamination was observed in Si(1 1 0) leading to a lower Coulombic efficiency. Continuous electrochemical deactivation of Si(3 1 1) was associated with delamination across the whole interface, Li trapping and formation of thick (ca. 60 nm) SiO2 structures. These results demonstrate surface crystallography to be a critical factor when designing Si‐based battery materials and strongly suggest that promoting Si(1 0 0) facets could potentially provide longer cycling life and performance due to a higher resistance to degradation. Abstract :